TAFSIR KEBAHAGIAAN (Studi tentang Makna Kebahagiaan Dalam Al-Qur’an Perspektif Tafsir ) - Didi Junaedi (UIN Siber Syekh Nurjati Cirebon, 2018)
This article focuses on the study of interpretations of the meaning of happiness in the Qur'an. From the results of the author's study, it was concluded that the Qur'an uses different terms to describe happiness. The saida term with its various derivatives shows happiness in the hereafter. While the term aflaha with its various derivatives shows the process of achieving happiness in the world and the hereafter. The Qur'an also distinguishes between pleasure or pleasure (al-farh, mata ‘) with happiness (al-Falah, al-Sa‘adah). From the results of the study the author shows that the Qur'an distinguishes the meaning of pleasure from happiness. Happiness does not merely fulfill desires or desires of lust alone, but also considers two important aspects in us, namely affective (emotion) and cognitive (logic). Real happiness can be achieved if we keep abiding by the rules and moral norms that apply. Happiness (happiness, al-sa‘adah) is different from pleasure (pleasure, al-farh, al-surur).